Magnesium Membrane Shield Technique for Alveolar Ridge Preservation: Step-by-Step Representative Case Report of Buccal Bone Wall Dehiscence with Clinical and Histological Evaluations - Marko Blašković; Ivana Butorac Prpić; Serhat Aslan; Dragana Gabrić; Dorotea Blašković; Olga Cvijanović Peloza; Marija Čandrlić; Željka Perić Kačarević (Biomedicines)
Background/Objectives: Despite the increased use of new resorbable magnesium membranes, there are no reported cases or studies on the use of resorbable magnesium membranes in combination with bone grafts for alveolar ridge preservation (ARP) in cases with severe buccal bone wall dehiscence. This case report aimed to evaluate the effectiveness of the magnesium membrane shield technique in conjunction with bone grafting for ARP, assessing both clinical outcomes and histological bone regeneration. Methods: A 44-year-old female patient presented with a vertical fracture on tooth 24 (FDI Notation System) accompanied with complete destruction of the buccal bone wall. The treatment plan included tooth extraction, ARP using a combination of anorganic bovine bone and autologous bone grafting, and the application of a magnesium membrane as a shield to the pre-existing buccal wall. Six months post-procedure, a bone biopsy was taken from the implant site using a trephine bur. Results: Clinical and radiological evaluations six months after the procedure demonstrated sufficient bone volume for implant placement. Additionally, in the next three months, soft tissue conditioning with a provisional crown resulted in an aesthetically and functionally satisfactory outcome. Histological analysis of the bone biopsy revealed well-formed new bone in direct contact with residual biomaterial, with no signs of inflammation. Osteocytes were clearly visible within the newly formed bone matrix, indicating successful bone maturation. Active osteoblasts were observed along the bone-biomaterial interface, suggesting ongoing bone remodeling and integration. Additionally, histomorphometric evaluation revealed 47% newly formed bone, 32% soft tissue, and 19% residual biomaterial. Conclusions: This case demonstrates the potential of the magnesium shield technique as an ARP technique in cases with severe buccal wall dehiscence. The technique yielded satisfactory clinical outcomes and promoted successful bone regeneration, as confirmed by histological analysis.